Pengelolaan Informasi dan Dokumentasi Sebagai Basis Pemenuhan Keterbukaan Informasi Publik - Diah, Arum Halimatusa; Maring, Prudensius (Ridwan Institute, 2024)
Achieving transparent public information access services requires good information management and documentation. For this reason, it is necessary to study the role of information and documentation management officials in supporting the realization of public information openness. This research uses a qualitative approach by applying interview, observation and documentation methods. The results of this research show that to realize openness of public information, information and documentation management officials at UINJ carry out the role of coordinating, documenting information, verifying information, testing consequences, updating information, and providing information to the public. To support the achievement of these roles, PPID UINJ refers to standard operating procedures and implementation of evaluations. However, the results of this research also show that the implementation of public information has not been optimal due to barriers to mindset regarding openness of public information and technical obstacles. Theoretically, the results of this research show that success in realizing public information openness is not only through fulfilling the indicators of the role of officials but also through changing the mindset of stakeholders and supporting work units in the work environment as a whole